(3GdYdGbGJ GdOhdjI GdESdGejI (B:s (3OQGSI ebGQfI aj GdbGfhf GdOhdj GdYGe (B= Islamic international relations: a comparative study in public international law /s - (3GdaJdGhj, Sgjd MSjf,s 1941- ((3YeGf, GdCQOf (B:s (3OGQ GdKbGaI ddfTQ hGdJhRjY,s, 2014)
(3jJfGhd cJGH (B((3GdYdGbGJ GdOhdjI GdESdGejI (B: (3OQGSI ebGQfI aj GdbGfhf GdOhdj GdYGe(B) (3hGdPj bGe HJCdjag GdOcJhQ (B%22(3Sgjd MSjf GdaJdGhj(B%22 (3aj MhGdj (B(336) (3UaMI ef GdbWY GdeJhSW ehVhY (B((3GdESdGe hGdYdGbGJ GdNGQLjI(B) (3eSJYQVG GdeMJhjGJ GdJGdjI (B: (3GdHGH GdChd (B: (3GdYdGbGJ GdOhdjI GdSjGSjI hGdOHdheGSjI GdESdGejI, GdYdGbGJ GdSjGSjI GdOhdjI aj UOQ GdESdGe GdChd, GdYdGbGJ GdOhdjI aj GdYghO GdESdGejI GdCNQi, GdYdGbGJ GdOHdheGSjI GdESdGejI, GdHGH GdKGfj (B: (3eXGgQ GdYdGbGJ GdOhdjI GdESdGejI, GdhSGFd GdSdejI dJShjI GdefGRYGJ GdOhdjI aj GdESdGe, GdeQcR GdbGfhfj ddCLGfH aj GdESdGe, Ke bGFeI GdeUGOQ hGdeQGLY(B.s
(3HHdjhLQGajI (B: (3UaMI (B321-334.s
Keywords: (3GdYdGbGJ GdNGQLjI (B((3bGfhf Ohdj(B)s; (3GdESdGe hGdYdGbGJ GdNGQLjIs